2005
DOI: 10.1123/japa.13.2.210
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Aging and 10 Years of Racing on Ultraendurance Running Performance

Abstract: The aim of this study was to examine the interaction between aging and 10 years of racing in endurance runners. Race-time data from 194 runners who had completed 10 consecutive 56-km ultramarathons were obtained. The runners were either 20.5 ± 0.7, 30.0 ± 1.0, 39.9 ± 0.9, or 49.4 ± 1.0 years old at their first race. Each runner’s race speed was determined for each race over the 10 years. Data were analyzed using repeated-measures ANOVA, one-way ANOVA, and independentttests and showed that performance improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…Knechtle and Nikolaidis [ 13 ] support these findings, with data for performances ranging from 6 h to 10 days’ duration, with the average age for peak performers at 6- and 10-day events being 44.8 years (43.9–45.7) and 44.6 years (42.9–46.3), respectively. SG was 47 years old when she set this WR and it is highly likely that experience and physiological changes related to her continuous training helped her complete this challenge [ 69 ]. Even with continuous training, ageing leads to reductions in VO 2max , velocity at lactate threshold, maximal heart rate, and muscle strength [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knechtle and Nikolaidis [ 13 ] support these findings, with data for performances ranging from 6 h to 10 days’ duration, with the average age for peak performers at 6- and 10-day events being 44.8 years (43.9–45.7) and 44.6 years (42.9–46.3), respectively. SG was 47 years old when she set this WR and it is highly likely that experience and physiological changes related to her continuous training helped her complete this challenge [ 69 ]. Even with continuous training, ageing leads to reductions in VO 2max , velocity at lactate threshold, maximal heart rate, and muscle strength [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…We corroborate the results of Knechtle et al [12], as the variable years running was not associated with race time for women in this 62 km race. Rae et al [28] examined the interaction of aging and racing on ultra-endurance running performance. Rae et al [28] found that that overall athletes (18 women, 176 men) took approximately four years to reach peak running speed for a 56 km ultra-endurance race.…”
Section: Discussionmentioning
confidence: 99%
“…For the race-experience category, the skiers were divided into inexperienced skiers comprising subjects who had completed the 90 km course less than four times and experienced skiers, that is, skiers with race experience from four or more races on the 90 km course. The differentiation between inexperienced and experienced skiers was based on the results showing that approximately four races in a 56 km ultramarathon were required to optimize performance, 20 and that athletes with less than 4 years of experience had a larger decrease in their pace during the course of a marathon compared with the decrease of the experienced athletes. 19 To investigate a specific category’s influence on the pacing profile during the VSR, the subjects were matched based on finish time, start group, and the other two categories to minimize their influence on the results of the statistical analysis.…”
Section: Methodsmentioning
confidence: 99%